Smaller, softer, lower-impedance electrodes for human neuroprosthesis: a pragmatic approach - Castagnola, Elisa; Ansaldo, Alberto; Maggiolini, Emma; Ius, Tamara; Skrap, Miran; Ricci, Davide; Fadiga, Luciano (Frontiers in Neuroengineering, 2014)
Finding the most appropriate technology for building electrodes to be used for long term implants in humans is a challenging issue. What are the most appropriate technologies? How could one achieve robustness, stability, compatibility, efficacy and versatility, for both recording and stimulation? There are no easy answers to these questions as even the most fundamental and apparently obvious factors to be taken into account, such as the necessary mechanical, electrical and biological properties and their interplay, are under debate. We present here our approach along three fundamental parallel pathways: we reduced electrode invasiveness and size without impairing signal-to-noise ratio, we increased electrode active surface area by depositing nanostructured materials and, we protected the brain from direct contact with the electrode without compromising performance. Altogether, these results converge towards high-resolution ECoG arrays that are soft and adaptable to cortical folds, and have been proven to provide high spatial and temporal resolution. This method provides a piece of work which, in our view, makes several steps ahead in bringing such novel devices into clinical settings, opening new avenues in diagnostics of brain diseases and neuroprosthetic applications.